Continuous Thymoquinone Administration Mitigates Sodium Iodate-Induced Retinal Degeneration in Rats - Erguven P.; Sevgin K.; Kotil T.; Kaleci B.; Caglar H. G.; ÖZER Ö. F. (My University, 2024)
Purpose: This study aimed to investigate the protective or therapeutic effect of thymoquinone (TQ) in a retinal degeneration rat model and its relationships with the retina ultrastructure, heme oxygenase 1 (HO-1), caspase-3, and RPE65 expressions and to determine whether TQ has a therapeutic effect at the biochemical level. Methods: A total of 25 adult Wistar albino rats were divided into the following treatment groups: saline (control: CONT), CO (corn oil), sodium iodate (SI), TQ + SI, and SI + TQ injection groups. Retina morphology, RPE65, HO-1, and caspase-3 expression levels were evaluated using immunohistochemistry, and optical density was determined using ImageJ. Ultrastructural evaluations were performed with electron microscopy. Thiol-disulfide homeostatic parameters were examined in serum samples. Results: Outer nuclear layer (ONL) thickness was significantly higher in the SI + TQ group compared to the SI group. The RPE65 expression significantly decreased in the SI group compared with the CONT and CO groups. A significant increase in RPE65 expression level and a significant decrease in caspase-3 expression level were found in the SI + TQ group compared with the SI group. The increase in HO-1 expression level was significantly higher in the TQ treatment groups, particularly in the SI + TQ group. In the SI and TQ + SI groups, the ONL thickness significantly decreased with a significant increase in caspase-3 expression compared to the CONT and CO groups. In the treatment groups, decreased organelle damage was observed on electron microscopy. In the SI + TQ group, the disulfide/native thiol and disulfide/total thiol ratios were significantly lower than all other groups, while the native/total thiol ratio was significantly higher than the other experimental groups. Conclusions: The present study provides evidence that continuous TQ treatment can increase HO-1 and RPE65 expression and decrease apoptosis (caspase-3 levels), thereby preserving the retina at the ultrastructural level. Moreover, TQ administration can maintain thiol/disulfide homeostasis in SI-induced retinal degeneration-modelled rats.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Sinirbilim ve Davranış; GÖZ HASTALIKLARI; SİNİR BİLİMİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; NEUROSCIENCE & BEHAVIOR; OPHTHALMOLOGY; NEUROSCIENCES; Oftalmoloji; Duyusal Sistemler; Hücresel ve Moleküler Sinirbilim; Ophthalmology; Sensory Systems; Cellular and Molecular Neuroscience; caspase-3; HO-1; Retinal degeneration; RPE65; Thymoquinone